Behind the Blue Line: Investigating Police Officers’ Attitudes toward Rape - Page, Amy Dellinger (Journal of police and criminal psychology, 2007)
The current study contributes to what is known about police officers’ attitudes toward rape. A survey was administered to 891 sworn police officers in two states in the southeastern United States. The surveys were designed to assess police officers’ acceptance of rape myths. It was hypothesized that police officers would be accepting of rape myths, which are inherently misogynistic. Attitudes toward rape were expected to vary according to educational attainment and experience with rape investigations, such that higher levels of education and more experience with rape investigations would lead to the rejection of rape myths. There was a significant difference in the acceptance of rape myths with varying levels of educational attainment and experience with rape investigations